A Comparative Analysis of "Madame Bovary" and "Anna Karenina": Exploring the Depths of Human Desires and Societal Constraints ("Conference on Universal Science Research 2023", 2023)
This article about the description of Gustave Flaubertʼs "Madame Bovary"and Leo Tolstoyʼs Anna Karenina books. The most powerful thing is in the world Literature. It can stop wars, struggles, and any problems. Literature is a hero of our life. It is a teacher, it is a friend and anything which is close you. It contains authentic works that have passed the test of time. Gustave Flobertʼs "Madame Bovary" and Leo Tolstoyʼs "Anna Karenina" are two timeless classics that explore the themes of affection, love, tensions, adultery and societal expectations. This essay aims to compare the characters, events, narrative styles in Madame Bovary and Anna Karenina. Highlighting the differences  and similarities between these masterpieces of Literature.This comparative analysis aims to examine the similarities and differences in the portrayal of Emma Bovary and Anna Karenina, shedding light on themes such as love, societal expectations, and the consequences of pursuing forbidden desires.